Chronic autoimmune urticaria : Where we stand ? - Goh C; Tan K (Wolters Kluwer Medknow Publications, 2009)
It is well-recognized that 30-40% of chronic idiopathic urticaria is autoimmune in nature. Chronic autoimmune urticaria is caused by anti-FcåRI and less frequently, by anti-IgE autoantibodies that lead to mast cell and basophil activation, thereby giving rise to the release of histamine and other proinflammatory mediators. Activation of the classical complement pathway and formation of C5a are important in dermal mast cell activation. C5a is also a neutrophil and eosinophil chemoattractant. Chronic autoimmune urticaria has been found to be associated with autoimmune thyroid disease. The autologous serum skin test is used as a screening test for chronic autoimmune urticaria and has a sensitivity and specificity of about 70 and 80%, respectively. The current gold standard diagnostic test is the basophil histamine release assay. The treatment of chronic autoimmune urticaria, as in chronic idiopathic urticaria, is with H1 antihistamines. Oral corticosteroids may be used during acute flares. Refractory cases have been shown to respond to cyclosporine and other immunomodulators. The prevalence of chronic autoimmune urticaria in Singapore is similar to that reported in Western countries at about 42%. The presence of thyroid autoimmunity appears to be higher than reported, with 22.5% of patients with chronic idiopathic urticaria here, exhibiting presence of thyroid autoantibodies.